Overview on the employment of the npl/cI587 regulation system in the overproduction of heterologous protein in escherichia coli culture - Firdausi Razali; Murray, Moo-Young; Scharer, Jeno S.; Glick, Bernard R.; Scientific Meeting (2004 : Melaka) (Skudai : Universiti Teknologi Malaysia, 2004)
53